Training Needs Of Teachers Of Integrated Hearing-impaired Children In Regular Schools (field Study In Some Elementary Schools Of The M’sila Province - Yahiaoui, Abdelkarim; Ouali , Fattoum (El Omda in Linguistics and Discourse Analysis, 2024)
Abstract: This study aimed to determine the training needs of teachers of hearing impaired children who are included in the regular schools of the state of Al-Messila from their point of view, based on the descriptive analytical approach, and the research community was composed of (12) teachers in February 2020, and the research tool was represented in Educational competency questionnaire for specialized education teachers - for the category of children with hearing impairment - prepared by Professor Farid ben kasmia from Abdul Rahman Mira University in Bejaia, for the purpose of data collection, where it was found that there are training needs for teachers of hearing impaired children who are included in regular schools. Key words: training needs - teachers - children with hearing impairment - school integration. Résumé: Cette étude visait à identifier les besoins de formation des enseignants des enfants malentendants intégrés dans les écoles ordinaires de la wilaya de M'sila selon leur point de vue, en utilisant la méthodologie descriptive analytique. La population de l'étude était composée de (12) enseignants en février 2020. L'outil de recherche était le questionnaire sur les compétences pédagogiques des enseignants de l'enseignement spécialisé - pour la catégorie des enfants handicapés auditifs - préparé par le professeur Farid Ben Kassemia de l'Université Abdelhamid Mira de Bejaia, et ce dans le but de collecter des données. L'étude a révélé qu'il existe des besoins de formation pour les enseignants des enfants malentendants intégrés dans les écoles ordinaires.